2018
DOI: 10.1007/978-3-030-03003-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Sustainable New Product Development Approach Based on Industry 4.0 Assets

Abstract: The consumption society becomes more and more complex and challenging for companies. Therefore, industries must adapt their capacities to drive and continually improve their processes, resources and data management in a competitive environment. This paper aims to bring together and to link the concepts of new product development (NPD) process, digital transformation and sustainable development through a human centered approach. Organization, Process and Knowledge Management are the main NPD's classic critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…(2018) highlighted Industry 4.0 enablers for supply chain sustainability and offered a research strategy to fill the gaps. Whereas Bibaud-Alves et al . (2019) used a human-centered approach to connect the ideas of new product development, digital transformation and sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) highlighted Industry 4.0 enablers for supply chain sustainability and offered a research strategy to fill the gaps. Whereas Bibaud-Alves et al . (2019) used a human-centered approach to connect the ideas of new product development, digital transformation and sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the collaborative process can be quite complex and sometimes marred by a lack of trust and destructive conflicts (Ndubisi, 2011). The use of advanced technologies in NPD management represents a huge opportunity to deal with their inherent complexity and to develop smart, connected products in a smart and connected industrial system (Bibaud-Alves et al , 2019; Kamble et al , 2020). The studies have observed a strong and inevitable linkage among product design, process design and production system design in a big data-driven Industry 4.0 environment (Patil et al , 2019; Kamble and Gunasekaran, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In their approach, the authors address the increasing need to capture knowledge of experiences regarding DT in Africa. Finally, Bibaud-Alves, et al [70] studied DT in a new product development (NDP) process introduced in a French furniture manufacturing company. The DT was motivated by a company crisis caused by both managerial and technical backwardness.…”
Section: E Red Clustermentioning
confidence: 99%